Evaluation of mechanization and computerization of books circulation systems in libraries - Janiūnienė, Erika (Information & Media, 1994)
This article deals with evolution of mechanization and computerization of books’ circulation systems. There are described the development of readers service in the different libraries from the first mechanized books’ card systems to the modern complex integrated computerized systems. Dickman’s, Gaylord’s and Brodart-Sysdak’s apparatus is noted as the first attempts to mechanize librarians work, as well as modern systems called LIBS 100 and SIBIL are considered.